When expanding Kinetic energy as(adsbygoogle = window.adsbygoogle || []).push({});

T=mc^{2}-m_{0}c^{2}

where m_{0}=rest mass and

m=m_{0}/sqrt(1-β^{2})

the first term correction is coming out to be -p^{4}/8m_{0}^{3}c^{2}

but taking T=E-m_{0}c^{2}

where E=sqrt(c^2p^2+m_{0}^{2}c^{4}) the correction is coming to be 3p^4/8m_{0}^{3}c^{2}

is there any contradiction?

**Physics Forums | Science Articles, Homework Help, Discussion**

Join Physics Forums Today!

The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

# I Special relativity

Have something to add?

Draft saved
Draft deleted

**Physics Forums | Science Articles, Homework Help, Discussion**